Optimalisasi Tata Kelola Keuangan Melalui Sinergi Pengabdian dalam Pengembangan Aplikasi Laporan Keuangan pada BUMDes Mekarsari - Devtian Putera Perdana; Diki Ardiansyah; Nur Azizah Wandinia Ghozali; Siti Annisa; Adinda Dwi Permatasari; Rahma Rina Wijayanti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This community service activity aimed to optimize the financial governance of BUMDes Mekarsari through two main stages: the Diagnostic and Problem Mapping stage, and the Intervention and System Optimization stage. The activity employed a descriptive qualitative method, utilizing observation, interviews, documentation study, application trials, and intensive mentoring. A Microsoft Excel-based financial reporting application was developed in accordance with the SAK EMKM structure to ensure ease of independent use by the management. As a result, BUMDes successfully compiled complete and accurate financial reports, with total assets increasing from IDR 15,556,885 to IDR 19,385,255 and a recorded net profit of IDR 708,675 in January 2025. This program led to increased accounting comprehension among partners, the formation of a disciplined recording culture, and the fulfillment of the team’s need for contextual, hands-on learning serving as a replicable model for other regions.